Influence of environmental factors on the development of storehouse fungus and fungi from the field (Eurasian Journal of Ecology, 2019)
The article shows the results of a study of the biological and environmental characteristics of fungithat damage crops. Seeds of grain crops were collected from granaries of Talgar, Ili, Karasai and Zhambyldistricts of Almaty region.728 samples of cereal seeds (Triticum aestivum L., Avena sativa L., Hordeum vulgare L., Zea mays L., Oryza sativa L., Sorghum) were collected. Based on studies of morphologicaland cultural characteristics, the following species of mushrooms are identified: Penicillium expansumLink, Aspergillus flavus Link, Rhizopus nigricans Ehrenb., Alternaria alternate (Fr) Keisse, Macrosporiumcommune Wall., Fusarium proliferatum (Matsush.), Alternaria tenuis Neees, West Africa, West Africa. ,Mucor mucedo Fres, Helminthosporium sativum Pammel, Cladosporium herbarium (Pers.) Link, Trichothecium roseum Link. In determining the damage to the types of fungi grain crops were used methodsfor determining the morphological and cultural characteristics, macroscopic. Depending on the morphological features of the species of fungi, the damaging grains were determined using the Naumov andLitvinov determinants. Identified environmental factors affecting the development of species of fungi.The effect of temperature and humidity on the growth and development of species of fungi was studied.Key words: fungi, grain seeds, field fungus, storage fungus,